Habitat and Density of Oviposition Opportunity Influences Aedes aegypti (Diptera: Culicidae) Flight Distance - Brown, Heidi E. (J Med Entomol, 2017)
Understanding the dispersal of Aedes (aegypti (L.) Diptera: Culicidae) after consuming a potentially infectious bloodmeal is an important part of controlling the spread of the arboviruses it transmits. Because of the impact on abundance, removal of oviposition sites is a key component of vector control. However, source reduction around a case may encourage dispersal of potentially infected vectors. We compare the effect of oviposition site availability on Ae. aegypti dispersal behavior within 30-m linear cages in three model ecosystems at the University of Arizona’s Biosphere 2 research facility. We found a significant interaction effect in which, when oviposition site density was sparse, dispersal was greater in the highly vegetated humid rainforest and limited in the low vegetation, arid desert model ecosystem. When oviposition site density was dense, no significant effect on dispersal was observed. These analyses support the idea that source reduction has an important influence on the distance that gravid, potentially infected, females will travel.